Anti-inflammatory activity of methanolic extracts from Ventilago harmandiana Pierre - Panthong A. (2014)
Methanolic extracts from the heart wood, stem bark, and stem wood of Ventilago harmandiana Pierre (Family Rhamnaceae) were assessed for anti-inflammatory effects using both acute and chronic inflammatory models. Analgesic and antipyretic activities of the extracts were also evaluated. It was found that all extracts possessed strong inhibitory effects on the acute phase of inflammation as seen in ethyl phenylpropiolate (EPP)- and arachidonic acid (AA)-induced ear edema as well as in carrageenin-induced paw edema in rats. The extracts elicited only weak inhibitory activity on cotton pellet-induced granuloma formation, a subchronic inflammatory model. In the analgesic test, all extracts exerted pronounced inhibitory activity in acetic acid-induced writhing response but showed only weak effects in the tail-flick test. The extracts also showed excellent antipyretic activity on yeast-induced hyperthermia in rats. © 2004 Published by Elsevier Ireland Ltd.